COMPARISON BETWEEN THE METHODS OF KRIGING AND FINITE ELEMENT ON THE ESTIMATION OF NIKEL LATERITE RESOURCE - FIRMANSYAH (NIM : 22106309), FERDY
Mineral resource (gold, nickel et cetera) generally is stated with the conventional model and non-deterministic (geostatistic) model. Geometry model is carried out with the conventional model in the form of the block/grid. Whereas in carrying out the estimation of the content, the method that is used is the geostatistic method. Although being regarded as adequate but it would be better if the method that is used has the basis similarity in geometry and content modelling. The Finite Element method with the basis of calculus (deterministic) has the limitations in handling some non-continuous object. This method cannot detect a limit that is not continuous when being undertaken. However despite of the weakness this method has the excellence in modelling an atypical object. The element can be adjustable in the modelling process. After the use in the calculation of coal resources is successful then this method will be used to count laterite nickel resources. The estimation of the laterite nickel resource is limited by Cut of Grade (Cog); for limonite nickel, the content of Ni ≥ 1.0% and Fe ≥ 25%; for saprolite nickel the content of Ni ≥ 1.4% and Fe ≤ 25%. The result of the Ni content estimation with the kriging method is 86.726 ton whereas with the element method is 74.830 ton. To determine the accuracy of the of laterite nickel resource calculation, we need a parameter that can be measured. So, cross-validation analysis is carried out to test the accuracy of estimation methods. The results from this test suggest that the finite element method can match the accuracy of the kriging method and even higher, so this method can be used in modelling and estimating the resources of laterite nickel. Results of the analysis also show that even more elements that are used then this method becomes increasingly accurate. This could be happened because this method is based on calculus in its approach.